Differential expression and methylation of integrin subunit alpha 11 and thrombospondin in the amnion of preterm birth - Jae Young Yoo; Young-Ah You; Eun Jin Kwon; Mi Hye Park; Sunah Shim; Young Ju Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThis study aimed to investigate the association between preterm birth and epigenetic mechanisms in the amnion.MethodsWe examined the association between differentially methylated regions (DMRs) and differentially expressed genes (DEG) using a cytosine-phosphate-guanine methylation array and whole-transcriptome sequencing from the amnion (preterm birth, n=5; full term, n=5). We enrolled 35 participants for mRNA expression analysis and pyrosequencing: 16 full-term and 19 preterm subjects. We compared the association of integrin subunit alpha 11 (ITGA11) and thrombospondin 2 (THBS2) gene methylation status with mRNA expression in the amnion.ResultsIn the preterm birth group, methylation of ITGA11 and THBS2 genes was significantly lower (ITGA11 gene: 60.30% vs. 73.16%, P<0.05; THBS2 gene: 64.59% vs. 73.16%, P<0.05), and the expression of the genes was significantly higher than that in the full-term group (ITGA11 gene: 14.20 vs. 1.57, P<0.01; THBS2 gene: 1.18 vs. 10.34, P<0.05).ConclusionMethylation of the ITGA11 and THBS2 genes in the amnion was associated with preterm birth. Thus, ITGA11 and THBS2 gene methylation status in the amnion may be valuable in explaining the mechanism underlying preterm birth.